The emergence of obesity among Australian Aboriginal children - Phillips, N; Henneberg, M; Norgan, N; Schmitt, L; Potter, C; Ulijaszek, S (Versita, 2013)
Obesity is of significant and growing concern among Australian Aboriginal children, and is linked to patterns of child growth. The aim of this paper is to show diverse patterns of growth and obesity emergence among Australian Aboriginal children using historical anthropometric data. Child growth in height, weight and body mass index (BMI) is reanalysed for children aged 2 to 19 years in Australian Aboriginal communities spanning two distinct time periods (the 1950s and 1960s; and the 1990s and 2000s) and six different geographical locations: Yuendumu, Haast’s Bluff, Beswick, Kalumburu, Gerard, and Raukkan. Comparisons of stature and BMI between the earlier and later years of measurement were made, and the proportion of children classified as overweight or obese by the International Obesity Task Force criteria estimated, to allow international comparison. Aboriginal children in the 1990s and 2000s were heavier, with higher BMI than those in the 1950s and 1960s, differences in height being less marked. While no children were classified as overweight or obese in the earlier period, 15% of males and 3% of females were classified so in the later period. The data suggests that the period of onset of the epidemic of overweight and obesity among rural Australian Aboriginal children was likely to have been between the 1960s and 1980s.